1981
DOI: 10.1042/bj1960803
|View full text |Cite
|
Sign up to set email alerts
|

2-Mercaptoacetate administration depresses the β-oxidation pathway through an inhibition of long-chain acyl-CoA dehydrogenase activity

Abstract: To elucidate the mechanisms through which 2-mercaptoacetate administration inhibits fatty acid oxidation in the liver, the respiration rates induced by different substrates were studied polarographically in rat hepatic mitochondria isolated 3 h after 2-mercaptoacetate administration. Palmitoyl-L-carnitine oxidation was almost completely inhibited in either the absence or presence of malonate. Octanoate oxidation was also inhibited, and the intramitochondrial acyl-CoA content was markedly increased. The oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 31 publications
3
31
2
Order By: Relevance
“…MA suppresses fatty acid oxidation by inhibiting the long-chain acyl-CoA dehydrogenases that catalyze mitochondrial ␤-oxidation (9). Bauché et al reported that octanoate oxidation was also markedly decreased after MA administration (14). Therefore the suppression of food intake by MCT preloading may be related to the hepatic ATP content.…”
Section: Discussionmentioning
confidence: 99%
“…MA suppresses fatty acid oxidation by inhibiting the long-chain acyl-CoA dehydrogenases that catalyze mitochondrial ␤-oxidation (9). Bauché et al reported that octanoate oxidation was also markedly decreased after MA administration (14). Therefore the suppression of food intake by MCT preloading may be related to the hepatic ATP content.…”
Section: Discussionmentioning
confidence: 99%
“…MA is a blocker of FA oxidation that acts through inhibition of long-chain acyl-CoA dehydrogenase activity in the mitochondrial matrix (2). Whether it also inhibits microsomal ␤-oxidation is unknown.…”
Section: Response Of Lipid and Glucose Metabolism To Mamentioning
confidence: 99%
“…injection of sodium 2-mercaptoacetate (MA; Sigma) after collection of the first blood sample. The drug, which blocks β-oxidation of fatty acids by inhibiting mitochondrial acyl-CoA dehydrogenase [19,20], was freshly prepared in ultra-pure water and injected at doses of 400 or 800 µmol/kg BW. These doses were chosen because MA at doses of 400 to 800 µmol/kg induces food intake in a dose-dependent manner during the light phase in rats maintained on a fat-supplemented diet [14].…”
Section: Experimental Protocolsmentioning
confidence: 99%